Impact of hybrid cooling approach on milling and surface morphological characteristics of Nimonic 80A alloy. (January 2022) - Ross, Nimel Sworna; Gopinath, C.; Nagarajan, Srinivasan; Gupta, Munish Kumar; Shanmugam, Ragavanantham; Kumar, M. Saravana; Boy, Mehmet; Korkmaz, Mehmet Erdi
Abstract: Poor surface traits, short insert life, high manufacturing costs, and low productivity are associated with the machining of nickel alloys. Cutting fluids have well-known positive and negative effects on machinability performance. As a result, the machining industry has developed green cutting environments such as vegetable oil assisted minimum quantity lubrication (MQL) and cryogenic cooling. Despite the fact that MQL and cryogenic approaches can replace mineral oil-based flooding, their lack of lubrication and cooling properties at high speeds have prompted a search for a new hybrid approach (CO2 + MQL) that provides adequate cooling/lubrication (C/L). Moreover, as of now, no information concerning the effects of hybrid cooling on milling of Nimonic-80A is existing. To test the viability, the machining of Nimonic-80A under hybrid C/L was compared to other cutting environments (MQL and cryogenic). As crucial machinability factors, temperature, power consumption, surface and subsurface characteristics were thoroughly examined. Hybrid condition curtailed the burr formation, which paves the way for a reduction in specific cutting energy (SCE). The experimental results indicate that the hybrid condition considerably decreases the temperature and SCE by 34–53% and 17–19% in comparison with the MQL condition. Peak widening and intensity reduction were seen in the XRD examination, but no phase transition was found. Smaller grain size shows the superiority of hybrid environment.